Use of Oral Communication Strategies in English Language by Graduate Students in an International Context - Najjari, Behrooz (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Students studying in international universities usually experience some difficulties and challenges when communication in English with students and people coming from different cultural and ethnic background. Nevertheless, to cope with challenges students may use Oral Communication Strategies (OCSs) but studies addressing these strategies in the international contexts have been rare. As such, this study was set out to identify a) the oral communication strategies used by the international students when communicating in English; b) to identify any possible differences in the use of OCSs used by students from different ethnic backgrounds; c) any possible gender differences in the use of OCSs used by the international students. The context of the study was Eastern Mediterranean University, Northern Cyprus, and the participants were 32 graduate (master's and PhD) students majoring in English Language Teaching (ELT) who were selected by convenience sampling who fell in five nationality groups (Turkish, Iranian, African, Iraqi& Others). This study adopted a mixed-method approach to address the questions under investigation. On the one hand the Oral Communication Strategy Inventory, adopted from Nakatani, provided quantitative data, and on the other hand, the oral communication task and semistructured interview along with observation and the researcher's field notes were triangulated to provide qualitative data. The quantitative data was analyzed through SPSS software and descriptive statistics, t-test and ANOVA tests were performed to provide answer to the research questions. The findings of the current study indicated that social affective, negotiation for meaning while speaking and message reduction and alteration were the next most frequently reported speaking strategies and negotiation for meaning while listening and nonverbal strategies while listening were the most frequently reported listening strategies by the international students. Comparing OCSs across different nationality groups showed that OCSs were not statistically significant across different nationality groups. However, gender differences were significant in two speaking strategies: social affective and negotiating for meaning while speaking with the females obtaining higher means than the males. The study yielded some important implications for practitioners, teachers and researchers who investigate this field of inquiry. Keywords: Oral Communication Strategies (OCSs), English Language Teaching (ELT), Social Affective, negotiating for meaning

ÖZ : Uluslararası üniversitelerde eğitim gören öğrenciler, farklı kültürel ve etnik geçmişlere sahip kişilerle İngilizce dilinde iletişim kurarken bazı zorluklar ve sorunlar yaşar. Bu zorluklarla başa çıkmak için öğrenciler sözel iletişim stratejilerini kullanabilir; ancak uluslararası bağlamda sözel iletişim stratejileriyle ilgili yapılan çalışmaların sayısı oldukça azdır. Bu nedenle, bu çalışma a) İngilizce dilinde iletişim kurarken uluslararası öğrencilerin kullandığı sözel iletişim stratejilerini, b) farklı etnik kökenlere sahip öğrencilerin sözel iletişim stratejileri kullanımındaki olası farklılıklarını ve c) uluslararası öğrenciler tarafından kullanılan sözel iletişim stratejilerinde olası cinsiyet farklılıklarını belirlenmeyi amaçlamaktadır. Çalışma, Kuzey Kıbrıs’ta bulunan Doğu Akdeniz Üniversitesi’nde, İngiliz Dili Eğitimi alanında eğitim gören 32 lisansüstü (yüksek lisans ve doktora) öğrencisi ile gerçekleştirilmiştir. Kolayda örneklem yöntemi ile seçilen katılımcılar, beş ana uyruk grubu (Türk, İranlı, Afrikalı, Iraklı ve Diğerleri) oluşturmaktadır. Bu çalışmada kullanılan soruları yanıtlayabilmek üzere karma yöntem yaklaşımı benimsenmiştir. Nicel veriler için Nakatani tarafından geliştirilen Sözel İletişim Stratejisi Envanteri kullanılırken, nitel veriler için sözel iletişim görevi, yarı yapılandırılmış görüşme, gözlem ve araştırmacının alan notları kullanılmıştır. Nicel veriler, SPSS yazılımı aracılığıyla ve betimleyici istatistikler ile analiz edilmiştir. Araştırma sorularını yanıtlayabilmek için t-test ve ANOVA testleri uygulanmıştır. Mevcut araştırmanın bulgularına göre, sosyal duygusal, konuşma sırasında anlam söyleşmesi ile mesaj eksiltme ve değiştirme’nin uluslararası öğrenciler tarafından en çok rapor edilen konuşma stratejileri oldukları görülürken, dinleme sırasında anlam söyleşmesi ve sözel olmayan stratejiler’in en çok kullanılan dinleme stratejileri oldukları görülmüştür. Farklı uyruklu gruplar karşılaştırıldığında, sözel iletişim stratejileri bağlamında farklı uyruklu gruplar arasında istatistiksel olarak anlamlı bir fark bulunamamıştır. Ancak, sosyal duygusal ve konuşma sırasında anlam söyleşmesi olmak üzere iki konuşma stratejisinde cinsiyete göre farklılık görülmüştür. Bu iki stratejide kadınların ortalamasının erkeklere kıyasla daha yüksek olduğu gözlemlenmiştir. Bu çalışma; pratisyenler, eğitimciler ve bu alanda araştırma yapan araştırmacılar için önemli çıkarımlar sağlamıştır. Anahtar Kelimeler: Sözel Iletişim Stratejilerini (OSCs), İngilizce Dilinde Iletişim (ELT), sosyal duygusal, konuşma sırasında anlam söyleşmesi
Master of Arts in English Language Teaching (ELT). Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2016. Supervisor: Assoc. Prof. Dr. Naciye Kunt.
Keywords: English Language Teaching (ELT); English Language - Study and Teaching; Oral communication - English Language; Oral Communication Strategies (OCSs); Social Affective; negotiating for meaning